The Antifungal Activity and Phytochemical Screening of a Traditional South American Remedy: Kyllinga vaginata Against Fusarium graminearum - Blanc R., Maria E. (2021)
KyllingavaginataLam. a native species of Paraguay, which is popularly known as "kapiikati", is marketed by Spanish hebalistsknown as "yuyeras". K. vaginataLam. has many pharmacologic effects such as diuretic, antispasmodic, diaphoretic, also used for the treatment of fungal diseases like leucorrhea. Its secondary metabolites are useful array of natural products with remarkable biological activities in medicinal components, food additives therapies, aromatic, and culinary purposes. In the current research phytochemical experiments revealed that the presence of several natural products in the rhizome of K. vaginata (ethanol crude extract), such as flavonoids, phenolic compounds and lipids. With the evidence of traditional anti-leucorrheauses, the present study also investigated to explore hidden alternative antifungal activity of K. vaginata.As a result of this translational approach, microorganism inhibition growth tests were performed on these crude EtOH extracts and revealed antifungal activity against Fusariumgraminearum, a phytopathogen of wheat. Useful identification features are cited for a fast/economic quality control of the rhizome of K. vaginata, the presence of secondary metabolites are declared and main chemical families of biologically active compounds are proposed for the first time for K. vaginata. Finally antioxidant activity of these roots were studied and the inhibitory activity against F. graminearum, proposed by this translational approach.